Destabilising microtubule polymerization regulates chondrocyte dedifferentiation and inflammation via nuclear factor kappa b and β-catenin pathway (Bangladesh Journal of Pharmacology, 2023)
The role of cell morphological changes in colchicine-inhibited tubulin polymerization of rabbit articular chondrocytes and their involvement in dedifferentiation were investigated. Colchicine treatment resulted in the dedifferentiation of chondrocytes, which was supported by the loss of type II collagen expression and proteoglycan production. Inhibition of tubulin de-polymerization with paclitaxel rescued colchicine-caused dedifferentiation and tubulin polymerization. Additionally, colchicine stimulated β-catenin overexpression, which is characterized by the accumulation of β-catenin into the cytosol determined by immunofluorescence staining. Inhibition of the β-catenin-mediated pathway by siR β-catenin recovered colchicine-caused the suppression of type II collagen expression in the chondrocytes. Treatment with colchicine also induced inflammation, as determined by the increased expression level of cyclooxygenase-2 and decreased IκB-α expression level by western blot analysis. Modulating the expression levels of pIκBα and IκBα via BMS 345541, was able to modulate colchicine-induced inflammatory effect.